Synergistic influence of cytokine gene polymorphisms over the risk of dementia: A multifactor dimensionality reduction analysis - Juárez-Cedillo, Teresa; Martínez-Rodríguez, Nancy; Vargas-Alarcon, Gilberto; Juárez-Cedillo, Enrique; Valle-Medina, Antonio; Garrido-Acosta, Osvaldo; Ramirez, Alfredo (Frontiers in Aging Neuroscience, 2022)
Objective Evidence supports the important role of neuroinflammation in some types of dementia. This study aimed to evaluate the effect of epistasis of gene cytokines such as interleukin (IL)-α, IL-6, tumor necrosis factor (TNFα), and interferon-gamma (IFN-γ) on the susceptibility to the development of dementia. Materials and methods In the study, 221 patients diagnosed with dementia and 710 controls were included. The multifactor-dimensionality reduction (MDR) analysis was performed to identify the epistasis between SNP located in genes of IL-α (rs1800587), IL-6 (rs1800796), TNFα (rs361525 and rs1800629), and IFNγ (rs2069705). The best risk prediction model was identified based on precision and cross-validation consistency. Results Multifactor-dimensionality reduction analysis detected a significant model with the genes TNFα, IFNγ, IL1α, and IL6 (prediction success: 72%, p < 0.0001). When risk factors were analyzed with these polymorphisms, the model achieved a similar prediction for dementia as the genes-only model. Conclusion These data indicate that gene–gene interactions form significant models to identify populations susceptible to dementia.